2001
DOI: 10.1088/0953-2048/14/9/321
|View full text |Cite
|
Sign up to set email alerts
|

Pinning mechanism of the peak effect in melt-processed Y-123 superconductors

Abstract: It is known that the peak effect in Y-123 superconductors is caused by oxygen deficient regions with lower T c . In order to study the flux pinning mechanism of these defects, the effect of the addition of 211 particles on the peak effect was measured. It was found that the addition of the 211 phase deteriorated the pronounced peak effect at medium magnetic fields. This suggests that the pinning mechanism of the oxygen deficient regions is repulsive and based on the kinetic energy interaction under the proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…4. It is known that the peak effect is caused by the transition of the vortex lattice in Cu oxide superconductors [15]- [18]. However, the reason for the first peak effect in present case is unknown.…”
Section: Resultsmentioning
confidence: 73%
“…4. It is known that the peak effect is caused by the transition of the vortex lattice in Cu oxide superconductors [15]- [18]. However, the reason for the first peak effect in present case is unknown.…”
Section: Resultsmentioning
confidence: 73%
“…ν 0 is the oscillation frequency of the flux bundle in the pinning potential well, and E c is the electric field criterion for determination of J c . Experimental and theoretical values of g 2 in Y-123 superconductor are shown in reference [17] and g 2 mostly takes on values ranging from three to four in a magnetic field parallel to the c-axis. In Bi-2212 single crystals or bulks [18] g 2 is estimated to be smaller than unity using equation (11), and the minimum value, g 2 = 1 for a single flux line, is used.…”
Section: Resultsmentioning
confidence: 99%
“…In previous measurements [7,8], it was found that J c decreased in the medium field region and the peak effect disappeared through the addition of 211 phase particles to Y-123 bulk superconductor. In addition, Mochida et al [9] found that the peak effect at medium fields decreased through the addition of Nd-422 particles in Nd-123.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, Mochida et al [9] found that the peak effect at medium fields decreased through the addition of Nd-422 particles in Nd-123. This means that the reduction in J cp is ascribed to the interference between the repulsive pinning (positive pinning energy) of lower-T c regions and the attractive pinning (negative pinning energy) of 211 phase particles (Nd-422 or Y-211) [8], suggesting that the pinning mechanism of lower-T c regions is not the attractive one, based on the field-induced pinning mechanism, a kind of condensation energy interaction. The expected mechanism of lower-T c regions is the repulsive kinetic energy interaction under the proximity effect [10].…”
Section: Introductionmentioning
confidence: 99%